SYSTEMATIC LITERATURE RIVIEW: THE EFFECT OF PBL LEARNING MODEL ON STUDENT’S CRITICAL THINKING ABILITY - Putri, Syifa Aulia; Waluya, Stevanus Budi (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Critical thinking is a very important skill for students to address the obstacles faced in this day and age. However, a number of studies show that Indonesian students have low levels of critical thinking, especially in mathematics. The problem-based learning (PBL) model is one method that can be used to overcome this problem. The Systematic Literature Review (SLR) method was used in this study to evaluate the problem-based learning (PBL) approach on improving critical thinking skills. Research published in the time span of 2018 to 2024 with related keywords were investigated. The analysis of 13 articles showed that the use of PBL improved students' critical thinking skills, especially in junior high school. These findings suggest that PBL should be applied as well as possible in the mathematics learning process to develop and improve students' critical thinking skills in Indonesia. Students' inability to explore and develop new ideas is a major obstacle in the application of PBL.